Marée arctique - Sanielevici, Alexandre (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1997)
Recording of Alexandre Sanielevici's Marée arctique. Arctic Mare is an electroacoustic suite of short linked episodes, which pass through several differing sonic atmospheres. The processed sounds are mainly from various machines such as computers, hard drives, modems, and CD mechanisms. Many of the same sounds, as well as their variations, are reused in different contexts throughout the piece, thus contributing to the unification of the piece in a natural evolution.